A Microstructure Based Strength Model for Slag Blended Concrete with Various Curing Temperatures - Li-Na Zhang; Wang Xiao-Yong; Kyung-Taek Koh (Advances in Materials Science and Engineering)
Ground granulated blast furnace slag, which is a byproduct obtained during steel manufacture, has been widely used for concrete structures in order to reduce carbon dioxide emissions and improve durability. This paper presents a numerical model to evaluate compressive strength development of slag blended concrete at isothermal curing temperatures and time varying curing temperatures. First, the numerical model starts with a cement-slag blended hydration model which simulates both cement hydration and slag reaction. The accelerations of cement hydration and slag reaction at elevated temperatures are modeled by Arrhenius law. Second, the gel-space ratios of hardening concrete are calculated using reaction degrees of cement and slag. Using a modified Powers’ gel-space ratio strength theory, the strength of slag blended concrete is evaluated considering both strengthening factors and weakening factors involved in strength development process. The proposed model is verified using experimental results of strength development of slag blended concrete with different slag contents and different curing temperatures.